The Impact of E-WOM (Electronic Word of Mouth) on Purchase Decisions on the Shopee Platform - Reni Silvia Yuli Safitri (Business Management, 2026)
The growth of digital business in today’s era influences consumer behavior, particularly when it comes to making decisions about purchasing or consuming a product; trust in Electronic Word of Mouth (e-WOM) has become a key factor in helping consumers make the right decisions regarding product consumption.  This study aims to analyze the influence of E-WOM (Electronic Word of Mouth) on purchasing decisions on the Shopee platform. The study employs a qualitative research method and uses literature review as the data collection technique. The results indicate that E-WOM influences purchasing decisions and can reduce purchasing risk by helping consumers mitigate the risk of product defects or evaluate product quality before making an online purchase.